EVALAUTION THE SENSITIVITY OF EXCHANGE RATE OF IRAQ BILATERAL AGRICULTURAL TRADE DURING THE PERIOD 1995-2014 - Al-Badri, Basim H. (Diyala Agricultural Sciences Journal, 2017)
This paper examines the short term and long term effects of changes of exchange rate on bilateral trade flows of agricultural products between Iraq and its major trading partners (Syria, Jordan and United Arab Emirates). In accordance with the J-curve theory, the Johansen cointegration test was employed to analyze the long term relationship and a vector error correction model to explore the short term effects of Iraqi Dinar exchange rate level. The data set used in this study covers period from 1995 to 2014. Agricultural product groups are based on the SITC classification. Results showed that if the Iraq foreign trade in agricultural sector is disaggregated into particular product categories, there can be found only some sectors significantly connected with exchange rate movements in the long term. The effects of exchange rate movements are less than ambiguous and cannot be generalized across the analyzed product categories. Theoretical short term and long term assumptions can not confirmed in trade of most of agricultural trade of Iraq with its most important partners